2015
DOI: 10.1002/hep.27859
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor kappa B–mediated CD47 up‐regulation promotes sorafenib resistance and its blockade synergizes the effect of sorafenib in hepatocellular carcinoma in mice

Abstract: Sorafenib is a new standard treatment for patients with advanced hepatocellular carcinoma (HCC). However, the survival benefit of this treatment is modest, partly owing to drug resistance. Recent evidence has demonstrated the existence of tumor-initiating cells (T-ICs) as the culprit for treatment resistance. To examine whether sorafenib resistance was a result of the presence of liver T-ICs, we developed sorafenib-resistant HCC cells both in vitro and in vivo through continuous exposure to sorafenib. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
136
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 33 publications
8
136
0
Order By: Relevance
“…Reported previously by us and others (60,61), SIRPα expression in macrophages is decreased following LPS stimulation, suggesting a dynamic nature for the CD47-SIRPα-mediated inhibition especially on infection or activation of TLR. The expression of CD47 on cells can also be changed under different conditions (62)(63)(64). Also reported by us, alteration of clustering structures of SIRPα on macrophages or CD47 on tissue cells affects phagocytosis (65,66).…”
Section: Discussionmentioning
confidence: 70%
“…Reported previously by us and others (60,61), SIRPα expression in macrophages is decreased following LPS stimulation, suggesting a dynamic nature for the CD47-SIRPα-mediated inhibition especially on infection or activation of TLR. The expression of CD47 on cells can also be changed under different conditions (62)(63)(64). Also reported by us, alteration of clustering structures of SIRPα on macrophages or CD47 on tissue cells affects phagocytosis (65,66).…”
Section: Discussionmentioning
confidence: 70%
“…Blocking the interaction of CD47 with its receptor, SIRPα, on macrophages enables phagocytosis and inhibits tumor growth (35,36,(44)(45)(46). However, the molecular mechanisms regulating the expression of CD47 by cancer cells have not been delineated.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here represent to our knowledge the first identification of a transcriptional regulator of CD47 expression in breast cancer cells and further studies are required to determine whether HIF-1 cooperates with other transcription factors that are induced by the tumor microenvironment, such as CREB, NF-κB, SMAD2, or STAT3. Increased NF-κB activity was observed in hepatocellular carcinoma cells that developed sorafenib resistance (36), which is of interest because the antiangiogenic effects of sorafenib induce intratumoral hypoxia that causes HIF-1-dependent induction of breast CSCs (19). Immunosuppressive functional interactions of HIF-1 and CREB have been proposed in T cells (47), but may also occur in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the notion that cancer cells frequently up-regulate CD47 compared to their normal counterparts is now widely accepted, the underlying up-and down-stream regulatory mechanisms are not fully elucidated. Previous studies including breast cancer identified that the promoter region for the CD47 gene is regulated by binding of several transcription factors, including MYC and NF-κB (8,9). However, the exact mechanism behind the overexpression of CD47 in cancer cells is insufficiently understood (10).…”
mentioning
confidence: 99%